Status of CSA adoption and related impact on farming communities across 8 CSV implementing the CSV monitoring plan in 2018 - Bonilla Findji, Osana; Bejarano, Gustavo; Eitzinger, Anton; Andrieu, Nadine (2019)
The Climate-Smart Village Multilevel Monitoring Framework developed by CCAFS consists of a set of 44 robust and standard indicators at household and at farm level, covering the Productivity/Food Security, the Adaptation and the Mitigation pillar of CSA and a friendly ICT-based data collection instrument that provides standard CSA metrics and can be rapidly, reliably and systematically deployed across the global CCAFS Climate-Smart Villages network. Between February and December 2018 it was implemented by locally trained enumerators across 8 CSV sites in LAM, EA and SA, interviewing over 2,300 farmers using the Smart Monitoring App for data collection. This report presents preliminary results of the analysis highlighting adoption levels of the targeted CSV practices and illustrative examples of the effects of the top three CSA options on livelihoods level indicators, including one that assesses the gender dimension (impact on labor).